Interrelationship between reproductive hormones and acute phase proteins during estrous cycle and pregnancy in Spanish purebred broodmares - Katiuska Satué (Elsevier, 2021)
In some species, female steroid hormones modify the profile of acute phase proteins (APPs) during the estrous cycle and pregnancy, according to the ovulation, embryonic implantation and placental development; however, nowadays there's no experimental evidence for equine species. Objectives of this study were: to compare the serum amyloid A (SAA), haptoglobin (Hp) and C-reactive protein (CRP) concentrations between cyclic and pregnant mares, and to analyze the influence of estradiol-17β (E2) during estrous cycle or estrone sulfate (E1) during pregnancy, and progesterone (P4) on these proteins to assess their potential role to identify the cyclicity or pregnancy in Spanish mares. Blood samples were taken from 20 Purebred Spanish mares on the day of ovulation (day 0), on days +5 and +16 post-ovulation, and then, monthly during the whole pregnancy. SAA, Hp and CRP did not change between day 0, +5 and +16 post-ovulation days. P4 concentrations were significantly higher on day +16 than on days +5 and 0; and E2 concentrations were significantly higher on day 0 than day +5. On the other hand, pregnancy was characterized by a progressive increase in the Hp, variable modifications of E1 and P4 concentrations, without changes in SAA and CRP. The absence of significant differences in the APPs between days 0, +5 and +16, suggested that these proteins cannot be used as biomarkers of diagnosis of heat or pregnancy in Spanish mares, at least early, since the Hp later increases during the gestation. Nevertheless, it is possible to use them for comparative purposes with other equine breeds, as supervisor instrument of health status in breeding females as diagnostic tools to monitor pregnancy's development and/or subclinical reproductive inflammations, that could lead to the early embryonic death.